Improving the Knowledge of Akidah (Faith in the Last Day) of Elementary School Students through Audio Visual Learning Videos - Mariani, Emilia Tri Puspita (Indonesian Journal of Research in Islamic Studies, 2024)
The main task and responsibility of a teacher is to create effective, efficient, creative, dynamic and fun learning. The purpose of this study was to determine the increase in knowledge of Akidah (Faith in the Last Day) SDN O2 Ipuh through audio visual learning videos. The type of research used is Classroom Action Research. The research was conducted at SDN 02 Ipuh in 2023, the research sample was class V students totaling 19 students. Data collection techniques in this study were obtained through observation and field data records, test results and notes on reflection/discussion results. Data analysis techniques used by researchers include (1) data collection; (2) verification / conclusion drawing; (3) data reduction. The results of the study obtained the conclusion that the use of teaching videos can increase can increase students' knowledge of akidah (faith in the last day). there are three factors that show the tendency that student learning activeness in the learning process is still low. First, students lack the courage to express their opinions to others. Second, students lack the ability to formulate their own debate. Third, students are not accustomed to competing in expressing opinions with other friends